Analisis Status Hak Pakai atas Tanah dan Bangunan pada Daerah Jalur Hijau terhadap Pajak Bumi dan Bangunan di Kelurahan Tuak Daun Merah Kota Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to (1) analyze the impact of land and building use-right status on the obligation to pay Land and Building Tax (PBB) in the green belt area of Tuak Daun Merah Sub-district; and (2) examine the influence of use-right ownership on the level of community compliance with PBB payments. The research employed a qualitative descriptive approach through observation, interviews, and document analysis. The findings reveal that the lack of legal clarity regarding land status is the primary factor contributing to low tax compliance. Many residents do not possess use-right certificates despite residing on state-owned or green belt land, leading to legal uncertainty. Some residents continue to pay PBB without formal legal documentation as an attempt to secure potential future administrative legitimacy, while the majority refrain from paying taxes due to concerns over legal consequences or possible evictions. This condition directly affects the fluctuation of PBB revenue and reduces the effectiveness of local tax collection. Therefore, strategic governmental measures are required to reorganize land status, clarify ownership rights, and formulate fair and sustainable tax policies in order to enhance local revenue (PAD).